Intercropping with post-grafting generation of Solanum photeinocarpum decreases cadmium accumulation in soybean (Glycine max). Issue 11 (19th September 2021) - Hu, Rongping; Li, Qinyuan; Huang, Yong; Zhao, Yan; Xiao, Ling; Jing, Qianhe; Zou, Yao; Lin, Lijin
Abstract: A pot experiment was designed to explore the effects of different post-grafting generations of Solanum photeinocarpum Nakamura et Odashima intercropping on growth and cadmium (Cd) accumulation in soybeans (varieties: "Zaodou" and "Liaoxian"). Post generation of S. photeinocarpum (ungrafted, grafted on eggplant, potato, and tomato, respectively) were utilized to intercrop with two varieties of soybean in Cd-contaminated soil. Soybean monoculture was employed as a control. Consequently, intercropping with different post-grafting S. photeinocarpum generation, except for tomato rootstock grafts post-generation, could reduce soybean biomass and photosynthetic pigment content. Additionally, all S. photeinocarpum post-grafting generations had the capacity to reduce Cd content in soybean when intercropping, while tomato rootstock grafts post-generation exhibited an adequate ability to accumulate Cd in S. photeinocarpum compared to the ungrafted treatment. In particular, tomato rootstock grafts post-generation could effectively decrease Cd content in soybean organs by 14.09–62.13%, relative to soybean monoculture, but increased shoot Cd content and shoot Cd extraction of S. photeinocarpum by 10.33–13.49% and 10.38–12.03%, respectively, compared to the ungrafted treatment. Thus, tomato rootstock grafting may enhance the ability of post-grafting generation of S. photeinocarpum to remediate Cd-contaminated soil, and this grafting was able to reduce Cd accumulation in soybean.